Poliovirus antibody levels and lameness among individuals in three regions of Ghana - Opare, Joseph Kwadwo Larbi (Hum Vaccin Immunother, 2019)
Introduction: Ghana recorded the last case of poliomyelitis caused by wild poliovirus in 2008 and the country was declared polio-free in 2015. Polio-neutralizing-antibody levels in the population of three geographically representative regions of Ghana was determined, to identify possible immunity gaps. Methods: Cross-sectional, hospital (1–70 years old) and school (primary, 1–15 years old)-based studies were undertaken in three regions in 2016. Individuals who visited the three teaching hospitals of the regions and were referred for haematology investigations were invited to participate in our study. Neutralizing-antibody titers to polio serotypes P1, P2, and P3 were assayed by WHO-standards. Antibody titers of ≥8 were considered protective. In the school lameness survey, clinical and epidemiological data were obtained from parents and their lamed children. Bivariate and multivariate analyses were conducted on subject characteristics, to assess potential factors for failure to seroconvert. P-values < 0.05 were considered statistically significant. Results: Neutralizing-antibodies against poliovirus types 1, 2 and 3 were detected in 86% (264/307), 84% (258/307) and 75% (230/307) of the samples, respectively. Overall, 60.1% (185/307) were seropositive for the three polio serotypes and 2.9% (9/307) were seronegative. Polio neutralizing-antibodies (P1and P2) decreased with age (p < .001). Low seroprevalence of polio-neutralizing-antibodies was significantly associated with low school attendance of mothers (p < .001). Prevalence of residual paralysis was <1.0/1,000 among the school children. Conclusion: Our study population is moderately protected against the three poliovirus serotypes. However, immunity appears to be lower with a higher age and low mother’s education. This may suggest the need for young-adult booster-dose to minimize the risk of wild poliovirus infection.